Experimental Study of Electric and Dielectric Behavior of PVC Composites - Madani, L.; Belkhir, K. S.; Belkhiat, S. (Engineering, Technology & Applied Science Research, 2020)
Polyvinyl chloride (PVC) is usually used as insulation in electrical engineering, mainly as cable insulation sheaths. A method for improving PVC’s dielectric properties, reducing the effects of UV aging, is the use of PVC films doped in alumina and titanium dioxide. This research investigated the influence of alumina and titanium dioxide (Al2O3/TiO2) on the dielectric properties of PVC. Four PVC samples were examined using an RLC impedance analyzer. Fourier Transform Infrared (FTIR) spectroscopy was utilized on the sample’s surfaces, exploring the chemical stability of the tested materials. In addition, the volume resistivity and average breakdown voltage of each sample were examined. Doping Al2O3/TiO2 into PVC improved its dielectric properties and volume resistivity while adding more ceramic decreased volume resistivity. Furthermore, the addition of Al2O3/TiO2 caused a significant enhancement in voltage breakdown strength.